Epidemiological evidence for a causal relationship between alcoholism and violence in colombia (2001)
A critical analysis of the epidemiological evidence to support a causal relationship between alcohol and violence in Colombia shows that there is a statistically significant association between patterns of consumption of alcohol and some types of violence even after adjusting for age, gender and social class. This association is weak but tends to increase with increasing expo sure. Evidence from animal experiments provide support for the effects of chronic consumption on aggressive behavior but not for acute consumption. As for the criteria of temporality, the percentage of perpetrators who consumed alcohol before aggressing another is highly variable. In addition, among a subgroup of perpetrators, aggressive behavior actually appears before initiation of alcohol consumption. The results of this analysis suggest that the evidence for a causal role of alcohol in the majority of cases of aggression is insufficient. Among those in which alcohol consumption appears to be more strongly associated, the appearance of aggressive behavior precedes alcohol consumption suggesting that both may be consequences of another and possibly common cause.